Human-animal interactions and opportunity to improve poultry welfare and productivity - Idrus, Zulkifli (2014)
Humans and poultry are in regular and at times close contact in modern intensive farming systems. The quality of human-animal interactions can have a profound impact on the productivity and welfare of poultry. Interactions by humans may be neutral, positive or negative in nature. Regular pleasant contact with humans may result in desirable alterations in the physiology, behaviour, health and productivity of poultry. On the contrary, birds that were subjected to aversive human contact were highly fearful of humans and their growth and reproductive performance could be compromised. Pleasant human contact may alter ability to tolerate various stressors through enhanced heat shock protein (hsp) 70 expression. The induction of hsp is often associated with increased tolerance to environmental stressors and disease resistance in animals. The attitude, behaviour, technical skills, knowledge, job motivation, commitment and job satisfaction of stockpeople are prerequisites for high quality stockmanship which will affect the birds’ fear of human and eventually their productivity and welfare.